Hamilton-Souplet-Zhang's Gradient Estimates for Two Types of Nonlinear Parabolic Equations under the Ricci Flow. (28th January 2016) - Huang, Guangyue; Ma, Bingqing
Abstract : We consider gradient estimates for two types of nonlinear parabolic equations under the Ricci flow: one is the equation u t = Δ u + a u log ⁡ u + b u with a, b being two real constants; the other is u t = Δ u + λ u α with λ, α being two real constants. By a suitable scaling for the above two equations, we obtain Hamilton-Souplet-Zhang-type gradient estimates.